PERSEPSI KOMUNITAS PEMUDA TANI TERHADAP UPAYA KONSERVASI SUMBER DAYA AIR DI WILAYAH DAS CISADANE HULU DESA PASIR BUNCIR KECAMATAN CARINGIN KABUPATEN BOGOR - Putri Diah Pandan Arum; Suminah Suminah; Bekti Wahyu Utami (Universitas Sebelas Maret, 2018)
This study examines internal and external factors of youth farmers community perception, examines the perception of youth community towards conservation of water resources, and to analyse the influence between the internal and external factors of the youth farmers community and the perception of the youth farmers community towards the conservation of water resources. The research location was chosen purposely in Pasir Buncir Village, Caringin Sub-district, Bogor Regency which is a village located in the Upper Cisadane River Basin of Penggerak Cisadane Hulu dan Lingkungan Hidup (PACING community center). Census sampling is34 members of PACING community. This research use multiple linear regression as an anlysis tools. The results showed that: (1) factors affecting perceptions such as non formal education are high, revenue is very low, experience is high, government agencies that play a role in socialization and assistance are Badan Pengelola DAS (BPDAS) and Dinas Kehutanan, four government agencies play a role in supervision , opinion leader is considered influential but passive, the existence of privatization is quite bad, and organizational culture is very good in mission implementation, consistency and member involvement, while adaptability is just good (2) perception of member of PACING community toward conservation effort is good, (3) factors that can influence perception of youth community significantly only non formal education factor, experience and organization culture, while other factors such as revenue, government role, opinion leader, impact of privatization, has no significant effect.